Moral Disengagement: Contemporary Research, Controversies and Prospects - Y.V. Zakharova (Современная зарубежная психология)
Moral disengagement is a concept proposed by A. Bandura; as a set of self-deception strategies that people resort to in order to maintain self-respect and positive self-esteem when committing immoral and unethical acts. Moral disengagement is associated with various types of antisocial behavior; its study is of great benefit to society and therefore has been attracting the attention of researchers since the end of the twentieth century. The article provides an overview of modern foreign research on moral alienation. The main directions of studying this phenomenon are described: theoretical and behavioral correlates, personal and contextual prerequisites, the role of moral alienation as a predictor and cognitive mediator, methods and tools for studying moral disengagement and its mechanisms, contradictions discovered by researchers and further prospects for study. Today, research into moral disengagement in the context of helping professions and IT development, bullying and cyberbullying; mechanisms of moral disengagement in specific areas; family factors of its manifestation; the creation of highly specialized questionnaires; as well as the construction of a unified model of moral disengagement looks promising. The study of moral disengagement opens up opportunities for the prevention of immoral and unethical behavior.